2014
DOI: 10.1371/journal.pone.0104257
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Kinetics in the Frequency of Peripheral CD4+ T Cells in Patients with Ulcerative Colitis Experiencing a Flare during Treatment with Mesalazine or with a Herbal Preparation of Myrrh, Chamomile, and Coffee Charcoal

Abstract: BackgroundWe found the first evidence of the efficacy of a herbal treatment with myrrh, dry extract of chamomile flowers, and coffee charcoal for ulcerative colitis (UC). However, the impact of the herbal treatment on the CD4+ T-cell compartment, which is essential for both the induction of UC and the maintenance of tolerance in the gut, is not well understood.AimTo analyze the frequency and functional phenotype of CD4+ T cells and of immune-suppressive CD4+CD25high regulatory T cells (Tregs) in healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Their flowers contain antioxidant and anti-inflammatory compounds such as bisabolol, chamazulene, apigenin, and luteolin [60] . Two random double-blind controlled studies on UC patients found that a chamomile preparation which also contained myrrh and coffee charcoal was as effective as mesalamine [61,62] . However, since the preparation contained many components, one cannot assign the beneficial effects to chamomile alone.…”
Section: Chamomilementioning
confidence: 99%
“…Their flowers contain antioxidant and anti-inflammatory compounds such as bisabolol, chamazulene, apigenin, and luteolin [60] . Two random double-blind controlled studies on UC patients found that a chamomile preparation which also contained myrrh and coffee charcoal was as effective as mesalamine [61,62] . However, since the preparation contained many components, one cannot assign the beneficial effects to chamomile alone.…”
Section: Chamomilementioning
confidence: 99%
“…Immunomodulatory effects have been demonstrated in the murine system, specifically on murine macrophages. A few studies have also shown an immunomodulatory potential in the human system specifically on macrophages ( 16 – 18 ). These studies employed single extracts derived from specific plant parts or solvent systems.…”
Section: Introductionmentioning
confidence: 99%